2020
DOI: 10.1021/acs.jpclett.0c03163
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Water Ordering Is Insufficient to Explain Ice-Nucleating Protein Activity

Abstract: Ice-nucleating proteins (INPs) found in bacteria are the most effective ice nucleators known, enabling the crystallization of water at temperatures close to 0 °C. Although their function has been known for decades, the underlying mechanism is still under debate. Here, we show that INPs from Pseudomonas syringae in aqueous solution exhibit a defined solution structure and show no significant conformational changes upon cooling. In contrast, irreversible structural changes are observed upon heating to temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…The intensity of the O–H stretch band, and therefore the interfacial water alignment, is significantly higher at low temperatures. 42 , 44 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intensity of the O–H stretch band, and therefore the interfacial water alignment, is significantly higher at low temperatures. 42 , 44 …”
Section: Resultsmentioning
confidence: 99%
“…The process of bacterial ice nucleation at warm temperatures requires an appropriate pH value and intact INP structures. 44 Moreover, the activity of both classes of bacterial INs is strongly influenced by specific interactions with ions. These interactions are highly relevant to correctly predict the ice nucleation efficiency of bacterial INs under natural conditions (e.g., in the atmosphere).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 , 7 , 17 Recent studies further showed that environmental factors (pH, salts, antifreeze proteins) can have very different effects on class A and class C INs. 11 , 18 20 Here, we use the high-throughput twin-plate ice nucleation assay (TINA) to investigate the ice nucleation activity of the lipids 1,2-dimyristoyl-3-trimethylammonium −propane (DPTAP), 1,2-dipalmitoyl- sn -glycero-3-phosphoglycerol (sodium counterion) (DPPG), 1,2-dipalmitoyl- sn -glycero-3-phosphorylethanolamine (chloride counterion) (DPPE), phosphatidylinositol (PI), lipopolysaccharides, and the effects of deuterated water, heat, and delipidation on the ice nucleation activity of P. syringae . 21 …”
mentioning
confidence: 99%
“…It has been reported that the βhelix region of this protein is the primary IN site [71,72] and its presence can be detected using FTIR techniques [73] from the amide-I region of its IR spectra. A study into the amide-I region of purified IN proteins from Snomax ® was published recently [74], where the authors concluded that heating above 55 • C caused irreversible changes to the protein structure which resulted in reduced IN activity. We demonstrated for the first time that heat treatment causes most of the β-helix secondary structure in untreated Snomax ® to convert to a β-sheet or strand like structure using FTIR, and our microfluidic setup was able to show an associated decrease in the IN temperature.…”
Section: Discussionmentioning
confidence: 99%